Encountering Kali : in the margins, at the center, in the West - McDermott, Rachel Fell; Kripal, Jeffrey J. (Jeffrey John), 1962- (University of California Press, 2003)
This title explores one of the most remarkable divinities the world has seen - the Hindu goddess Kālī. She is simultaneously understood as a blood-thirsty warrior, a goddess of ritual possession, a Tantric sexual partner, and an all-loving, compassionate mother.